Pdgfra and Pdgfrb genetically interact during craniofacial development. Issue 6 (5th April 2016) - McCarthy, Neil; Liu, Jocelyn S.; Richarte, Alicia M.; Eskiocak, Banu; Lovely, C. Ben; Tallquist, Michelle D.; Eberhart, Johann K.
Abstract : Background: One of the most prevalent congenital birth defects is cleft palate. The palatal skeleton is derived from the cranial neural crest and platelet‐derived growth factors (Pdgf) are critical in palatogenesis. Of the two Pdgf receptors, pdgfra is required for neural crest migration and palatogenesis. However, the role pdgfrb plays in the neural crest, or whether pdgfra and pdgfrb interact during palatogenesis is unclear.Results: We find that pdgfrb is dispensable for craniofacial development in zebrafish. However, the palatal defect in pdgfra;pdgfrb double mutants is significantly more severe than in pdgfra single mutants. Data in mouse suggest this interaction is conserved and that neural crest requires both genes. In zebrafish, pdgfra and pdgfrb are both expressed by neural crest within the pharyngeal arches, and pharmacological analyses demonstrate Pdgf signaling is required at these times. While neither proliferation nor cell death appears affected, time‐lapsed confocal analysis of pdgfra ; pdgfrb mutants shows a failure of proper neural crest condensation during palatogenesis.Conclusions: We provide data showing that pdgfra and pdgfrb interact during palatogenesis in both zebrafish and mouse. In zebrafish, this interaction affects proper condensation of maxillary neural crest cells, revealing a previously unknown interaction between Pdgfra and Pdgfrb during palate formation. Developmental Dynamics 245:641–652, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: pdgfra and pdgfrb genetically interact in palatogenesis. Neural crest conditional loss of both Pdgfra;Pdgfrb in mouse causes exacerbated craniofacial defects compared to either mutant alone. pdgfra and pdgfrb are co-expressed in the neural crest beginning at 16 hpf, when maxillary neural crest begin to condense upon the oral ectoderm. In zebrafish, maxillary neural crest condensation is defective in pdgfra;pdgfrb double mutants.